Text Sentiment Analysis Based on Transformer and Augmentation - Gong, Xiaokang; Ying, Wenhao; Zhong, Shan; Gong, Shengrong (Frontiers in Psychology, 2022)
With the development of Internet technology, social media platforms have become an indispensable part of people's lives, and social media has been integrated into people's life, study, and work. On various forums such as Taobao and Weibo, a large number of people's footprints are left all the time. It is these chats, comments, and other remarks with people's emotional evaluations that make up part of public opinion. Analysis of this part of the network public opinion is conducive to maintaining the peaceful development of society. Therefore, sentiment analysis has become a hot research field. Sentiment analysis has made great strides as one of the hot topics in the field of natural language processing. Currently, the BERT model and its variants have achieved excellent results in the field of NLP. However, these models cannot be widely used due to huge demands on computing resources. Therefore, this paper proposes a model based on the transformer mechanism, which mainly includes two parts: knowledge distillation and text augmentation. The former is mainly used to reduce the number of parameters of the model, reducing the computational cost and training time of the model, and the latter is mainly used to expand the task text so that the model can achieve excellent results in the few-sample sentiment analysis task. Experiments show that our model achieves competitive results.